2021
DOI: 10.1016/j.radonc.2020.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Differential transcriptome response to proton versus X-ray radiation reveals novel candidate targets for combinatorial PT therapy in lymphoma

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 67 publications
3
9
0
Order By: Relevance
“…The obtained results indicated that, besides stemness, the repair of proton-induced complex DNA DSBs is a key determinant of intracellular sensitivity. We also observed a higher amount of residual ɣH2AX foci indicative of unrepaired DNA DSBs after proton irradiation in comparison with photons, which supports the notion that proton irradiation results in more complex DNA damages, especially at regions with a higher LET (Carter et al, 2018;Cuaron et al, 2016;Fu et al, 2012;Hojo et al, 2017;Oeck et al, 2018;Sertorio et al, 2020;Vitti and Parsons, 2019). Besides direct DNA damages, high intracellular ROS levels contribute to indirect DNA damages and other cytotoxic effects.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The obtained results indicated that, besides stemness, the repair of proton-induced complex DNA DSBs is a key determinant of intracellular sensitivity. We also observed a higher amount of residual ɣH2AX foci indicative of unrepaired DNA DSBs after proton irradiation in comparison with photons, which supports the notion that proton irradiation results in more complex DNA damages, especially at regions with a higher LET (Carter et al, 2018;Cuaron et al, 2016;Fu et al, 2012;Hojo et al, 2017;Oeck et al, 2018;Sertorio et al, 2020;Vitti and Parsons, 2019). Besides direct DNA damages, high intracellular ROS levels contribute to indirect DNA damages and other cytotoxic effects.…”
Section: Discussionsupporting
confidence: 82%
“…To summarize, proton irradiation significantly reduces the clonogenic survival of PCa and GBM but not HNSCC cell lines in comparison with photons. Our results support the body of literature indicating the induction of more complex DNA damages and delayed repair as one of the underlying mechanisms (Carter et al, 2018;Cuaron et al, 2016;Fu et al, 2012;Hojo et al, 2017;Oeck et al, 2018;Sertorio et al, 2020;Vitti and Parsons, 2019). However, we found no increase in oxidative stress following proton irradiation in comparison with photons.…”
Section: Proton Irradiation Induces Long-lasting Dna Damagessupporting
confidence: 91%
See 2 more Smart Citations
“…Many primary cells have been shown to primarily undergo accelerated senescence from low-LET radiation, but apoptosis can be observed at higher total doses of low-LET radiation (>50 Gy) [ 127 , 136 ]. Studies of cancer and normal cells have provided evidence that the biological “decisions” for non-survival versus survival are guided by signaling pathways, activated downstream of the initial DNA damage response, that are influenced by numerous characteristics specific to each cell type and its environment [ 114 , 123 , 133 , 135 , 136 , 138 , 139 , 140 , 141 ].…”
Section: Signal Transduction By High and Low Letmentioning
confidence: 99%